2005
DOI: 10.1007/bf03192645
|View full text |Cite
|
Sign up to set email alerts
|

Winter diets of wolfCanis lupus and lynxLynx lynx in Estonia and Latvia

Abstract: O., Ozolins J. and Bagrade G. 2005. Winter diets of wolf Canis lupus and lynx Lynx lynx in Estonia and Latvia. Acta Theriologica 50: 521-527.Winter diets of wolf Canis lupus Linnaeus, 1758 and lynx Lynx lynx Linnaeus, 1758 in Latvia and Estonia were investigated in 1997-2000 based on stomach contents of hunted animals and scats. Ungulates appeared to be the staple food for both predators. Lynx diet to a high extent consisted of cervids (Estonia 52% frequency of prey, Latvia 88%), roe deer dominating. Mountain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…The few studies conducted in the Baltic region (Valdmann et al, 1998(Valdmann et al, , 2005Andersone, 1999;Andersone & Ozoliņš, 2004) confirm the existing knowledge; however, they have significant implications related to the species conservation policy.…”
Section: Introductionsupporting
confidence: 63%
“…The few studies conducted in the Baltic region (Valdmann et al, 1998(Valdmann et al, , 2005Andersone, 1999;Andersone & Ozoliņš, 2004) confirm the existing knowledge; however, they have significant implications related to the species conservation policy.…”
Section: Introductionsupporting
confidence: 63%
“…Although the majority of feeding is carried out during winter to decrease mortality during the coldest months, some supplementary feeding also occurs in summer, with the intention of keeping animals within the borders of particular hunting districts. In Estonia, wild boar is a preferred prey item for wolf (Canis lupus) (Valdmann et al 1998) and may occasionally be preyed upon by brown bear (Ursus arctos) (Vulla et al 2009) and Eurasian lynx (Lynx lynx) (Valdmann et al 2005). However, in general, large carnivores are not very abundant in Estonia and seem unlikely to be capable of limiting boar numbers-the number of wolves in Estonia is kept below 200.…”
Section: Study Areamentioning
confidence: 97%
“…Several studies have demonstrated that, where natural conditions are present, wild ungulates are staple Table 1 Red fox and wolf annual and seasonal diets in Alpe di Catenaia, Italian Apennines. Data are expressed as average volume (AV%) and frequency of occurrence (FO% in brackets prey for wolves Capitani et al 2004;Gazzola et al 2005;Valdmann et al 2005). Although studies conducted in Central European regions showed that, among wild ungulates, wolves preferred cervids (Jędrzejewska et al 1994;Okarma et al 1998), several studies in Italy Mattioli et al 1995Mattioli et al , 2011 pointed out that wild boar was the most important prey for wolf.…”
Section: Discussionmentioning
confidence: 99%